The Impact of IFRS 9 on Financial Reporting during Covid-19 from the Point of View of Experts in Europe - Ildikó Orbán; Oday Tamimi (Australasian Accounting, Business and Finance Journal, 2023)
The present study aimed to clarify the risks that banks are exposed to in light of the Covid-19 pandemic, examine the impact of these risks on the quality of financial reports in banks, with an indication of how IFRS 9 can either exacerbate or mitigate these risk and its effects on the financial statements of banks. Finally, provide some solutions to maintain capital adequacy and minimize pandemic risks to which some banks may be exposed. This study used the descriptive and inferential statistics, as well as the questionnaire as a tool for collecting data. The analysis of data by using the statistical program SPSS 25 and Microsoft Excel. Three major findings are outlined in this study. First, there is a statistically significant relationship between Covid-19 pandemic and the increased risks to which banks are exposed based on the results of the tests of the hypotheses. Second, there is a statistically significant relationship between IFRS 9 and the quality of the financial statements. Finally, there is a statistically significant relationship between IFRS 9 and bank risks during of the Covid-19 pandemic. The findings of this study are important for bank executives, auditors, and bodies that set standards for accounting and auditing.
Keywords: IFRS 9; Covid-19 Pandemic; Financial Instruments; Financial Reporting